PENGAWASAN TERHADAP PENANGANAN ANAK JALANAN OLEH DINAS SOSIAL, PEMUDA DAN OLAHRAGA DI KOTA SEMARANG - Aprianna Marselina Sinabutar; Endang Larasati Setianingsih (Journal of Public Policy and Management Review, 2017)
The mandate in The 1945 Constitution of Republic Indonesia article 34 is that impoverished people and abandoned children shall be taken care by the State. The State ensure the life sustainibility of all of the people without any exception. The local government with its principle of autonomy determine and manage its own needs, including the government of Semarang City. The realization of the mandate in The 1945 Constitution of Republic Indonesia is the Social, Youth, and Sports Board of Semarang City. This board’s duty is executing the governement’s affairs in socials matters including the abandoned children. The Social, Youth, and Sports Board needs to do formulating policies as the reference in excecution of duties, coordinating with related parties, coaching, providing facilities, and the most important thing is controlling the surveillance carried. Therefore, this research aims to understand and describe controlling process of abandoned children handling by the Social, Youth, and Sports Board of Semarang City. This research used descriptive qualitative method. The data sources are taken from informants, occurences in field, and the documents from the Social, Youth, and Sports Board of Semarang City. The data collection techniques include interview, documentation, and observation.. The results showed that: the achievement of these treatment programs can not be run with the maximum. Therefore in need of cooperation among relevant agencies and openness to one another and do not apply egos.